Content Production Strategy of Instagram @globalyouth.amb in Developing Generation Z Volunteerism - Bhojwani, Khayrani Kamal; Maryani, Eni; Rahmawan, Detta (COMMENTATE: Journal of Communication Management, 2023)
This research focuses on understanding the content production strategy of Instagram @globalyouth.amb (Global Youth Ambassador) in developing Generation Z volunteerism. The study uses a qualitative approach with a case study method. Data collection involves observing the @globalyouth.amb Instagram account's social media activities and conducting in-depth interviews with Global Youth Ambassador (GYA) stakeholders, followers, and social media professional. The study reveals effective strategies employed by @globalyouth.amb in engaging Generation Z in volunteer activities, focusing on three critical aspects, selecting topics, crafting compelling storylines, and strategic utilization of various Instagram features for content production. The meticulous topic selection process involves a blend of informative and persuasive content pillars, emphasizing trend adaptation. The incorporation of documentation content proves pivotal in enhancing program credibility. The study underscores @globalyouth.amb's active role in shaping positive narratives, utilizing Instagram features strategically, and maintaining a responsive approach, contributing to its success in fostering active participation in the context of volunteerism among Generation Z.